Operational analysis of motorized and non-motorized vehicle flow at intersection of Changying anf Wanshow roads - Hui, Zhang (2013)
With the rapid development of society, the transportation is more and more important in our country. That's why more and more traffic problems need to solve. Speed limit in the urban area at Xi'an city is already quite low at 40km/h, and this posses major problem at intersection where the traffic has to slow down at least by 50% of the speed limit as to allow vehicle from other directions to pass through; worst still having mixed mode of motorized and non- motorized vehicles at the same time The better to solve these problems are improving the road network and the traffic system. For this project, to determine the limit of capacity for the intersection based on three scenarios (mixed mode, bus and other motorized vehicles and bicycle only) as to analysis the severity of the problem According to these conditions the project will show the best intersection for the case. This research can apply the modern road network and improve the traffic system by analysis and design the new intersection, the suitable design can save cost, increase the speed through the intersection, and fully utilize space area. some common traffic problems can be relieved.